2008
DOI: 10.1590/s0103-97332008000500001
|View full text |Cite
|
Sign up to set email alerts
|

Leptonic decays of the B charged meson and B → Xsγ in the Two Higgs Doublet Model type III

Abstract: We consider the Two Higgs Doublet Model (2HDM) of type III which leads to Flavour Changing Neutral Currents (FCNC) at tree level. In the framework of this model we calculate the NLO contribution for b → sγ and the branchings for the meson decays B + → l + ν. We examine the limits on the new parameters λ bb and M H ± . We take into account the relationship between λ tt and λ bb coming from the validness of perturbation theory.Keywords: B Meson decay; 2HDM type III; Charged Higgs mass The Standard Model (SM) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Other bounds on the λ ij do not involve flavour-changing neutral currents. If one assumes that only λ tt and λ bb are nonzero, then neutral scalars play no role, and one can bound λ tt and λ bb by considering the charged-Higgs contributions to b → sγ [232,233,234]; one obtains a bound on λ tt of approximately 1.7, for a charged-Higgs mass below 300 GeV. More recently, Mahmoudi and Stal [46] analysed b → sγ and ∆m B d as well as B, K, and D s decays, and obtained bounds on all the second-and third-generation diagonal λ ij (including for the leptons).…”
Section: The Type III 2hdmmentioning
confidence: 99%
See 1 more Smart Citation
“…Other bounds on the λ ij do not involve flavour-changing neutral currents. If one assumes that only λ tt and λ bb are nonzero, then neutral scalars play no role, and one can bound λ tt and λ bb by considering the charged-Higgs contributions to b → sγ [232,233,234]; one obtains a bound on λ tt of approximately 1.7, for a charged-Higgs mass below 300 GeV. More recently, Mahmoudi and Stal [46] analysed b → sγ and ∆m B d as well as B, K, and D s decays, and obtained bounds on all the second-and third-generation diagonal λ ij (including for the leptons).…”
Section: The Type III 2hdmmentioning
confidence: 99%
“…Of course, if additional λ ij are taken to be non-zero the parameter space becomes quite large. Some recent analyses that discuss other λ ij include the work of Diaz et al [367], in which the effects of non-zero λ sb and λ tc were discussed (λ sb was found to be unbounded, λ tc was found to be smaller than 1), and of Idarraga et al [368], who also considered bounds from leptonic B decays but chose very large λ µµ and λ τ τ . Also note that, if neutral fields are allowed in the loop, one could get an effect proportional to λ 2 bs , which is, however, negligible.…”
Section: Models With Tree-level Flavour-changing Neutral Currents 421...mentioning
confidence: 99%
“…[11,12,13]) used various combinations of flavor and electroweak observables to constrain the parameter space of the type-II 2HDM, which garnered most of the attention because of its property of having the same Higgs-sector realization as the Minimal Supersymmetric Standard Model (MSSM). Other studies [14,15,16] explored the parameter space of 2HDMs unconstrained by a Z 2 symmetry, with the second Higgs doublet still in the (1, 2) 1/2 representation.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of the present study is to look for the constraints on all physical Higgs masses and coupling parameters in the light of the rare B-meson decays. In the framework of the 2HDM type III Yukawa interaction, the Cheng-Sher-Yuan (CSY) parameterization [39,40] for the couplings ε ij = m i m j v 2 λ ij is useful and among these, the third family couplings λ bb and λ tt are constrained, along-with charged Higgs boson mass, from the branching ratios of b → sγ and B + → l + ν [41]. They have shown that the most stringent constraints are coming from b → sγ and the pure leptonic decays can only exclude regions with small λ bb and small m H ± .…”
Section: Overview Of Two Higgs Doublet Modelmentioning
confidence: 99%
“…parameterization [39,40] for the couplings ε ij = m i m j v 2 λ ij is useful and among these, the third family couplings λ bb and λ tt are constrained, along-with charged Higgs boson mass, from the branching ratios of b → sγ and B + → l + ν [41]. They have shown that the most stringent constraints are coming from b → sγ and the pure leptonic decays can only exclude regions with small λ bb and small m H ± .…”
Section: Overview Of Two Higgs Doublet Modelmentioning
confidence: 99%